GAME EDUKASI FISIKA BERMUATAN LITERASI SAINTIFIK DAN ETNOSAINS PADA MATERI HUKUM NEWTON TENTANG GERAK - Socrates, Tegar Putra; Ikram, Riziqul; Afrizon, Renol; Hidayat, Rahmat; Hidayati, Hidayati; Rozi, Nur Erwani (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
The development of science and technology has changed the demands of the world of education. The national education system requires students to have scientific literacy competencies. The independent curriculum emphasizes the formation of Pancasila student profiles. One of the efforts made is to integrate local wisdom in learning. This curriculum adjustment requires the use of technology in learning. One solution is to develop an educational physics game. The study aimed to determine the characteristics, validity, and practicality of Physics educational games containing scientific literacy and ethnoscience. The research included the type of development research using the Plomp model. Research is limited to the stage prototyping phase at the small group practicality stage. The data source was obtained from the results of expert validation by Physics lecturers Faculty of Mathematics and Natural Sciences UNP. The source of practical data was acquired from grade X students of Senior High School 1 Padang. The data collection instruments in this study are validity test sheets and practicality test sheets. The data analysis technique used is descriptive statistical analysis. Based on the study results, the material validity test obtained a value of 0.88, and the media validity has a value of 0.92, each categorized as high validity. The results of the practicality test got a one-to-one stage value of 91.88 and a small group of 90.37; each categorized as very practical. It was concluded that physics educational games are valid and practical to use as a medium for learning Newton's laws of motion.